EXPLANATION OF THE APPLICATION OF SAK EMKM IN MICRO, SMALL AND MEDIUM ENTERPRISES - Feby Ramadhani Hariyono (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to find out how the application of SAK EMKM in the preparation of MSME financial reports and what are the obstacles faced by MSMEs in preparing financial reports. This research uses descriptive qualitative research method. Data collection techniques used are observation, interviews, and documentation. The results of the study indicate that MSME Bersama Jaya does not apply SAK EMKM in the preparation of its financial statements, because the owners of MSME Bersama Jaya do not understand SAK EMKM regarding the presentation of financial statements. The owner considers that the records made are clear and effective. The obstacles for UMKM Bersama Jaya in implementing SAK EMKM, are the lack of knowledge of the owners of UMKM Bersama Jaya about SAK EMKM, the lack of professional accounting staff at UMKM Bersama Jaya, and the owners do not understand recording and preparing financial reports.